PRODUCTION PERFORMANCE EVALUATION OF PRE-LAYING PERIOD AT 3 STRAINS OF GPS BROILER CHICKEN IN INDONESIA - Bestari, Ahmad; Darwati, Sri; Ulfah, Maria; Muladno, Muladno (Fakultas Peternakan, Universitas Padjadjaran, 2023)
The production performance of GPS on Cobb, Indian River, and Hubbard strains has not been well studied. This study aimed to compare the production performance between female GPS strains at 24 weeks of age and the standards set by each principal. This research was conducted from November 2022 to March 2023. The results showed a significant difference in most production performance between GPS strains at 24 weeks of age by each strain. Significant differences were observed for body weight, feed consumption, depletion and uniformity. As for comparing the production performance between the GPS strains and the standards set by the principal, there were also significant differences, and several performance parameters exceeded the standards. This result was influenced by different farming management patterns from each company adapting to actual conditions in the field.